1975
DOI: 10.2337/diab.24.9.851
|View full text |Cite
|
Sign up to set email alerts
|

Immunoreactive Glucagon Responses to Intravenous Tolbutamide in Chronic Pancreatitis

Abstract: The effects of tolbutamide infusion (1 gm. over forty minutes) on plasma pancreatic glucagon-like immunoreactivity (PGLI), serum insulin, and blood glucose were studied in six patients with chronic pancreatitis and six matched controls.asal PGLI levels were significantly higher in the patients, despite higher fasting glucose concentrations. Tolbutamide infusion had no significant effect on mean PGLI levels in controls but was associated with significant elevation in pancreatitis patients, despite higher circul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1977
1977
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The plasma IRG responses in tolbutamide tolerance test carried out in our laboratory on five normal subjects were decreasing during the initial ten minutes followed by elevation in concert with hypoglycemia . Kalk et al (1975) described how tolbutamide injection elevated the plasma pancreatic glucagon level in patients with chronic pancreatitis. Samols et al (1969) reported a suppressive response of plasma IRG to tolbutamide in a case with glucagonoma.…”
Section: Immunochemical Analysis Of the Tissuesmentioning
confidence: 99%
“…The plasma IRG responses in tolbutamide tolerance test carried out in our laboratory on five normal subjects were decreasing during the initial ten minutes followed by elevation in concert with hypoglycemia . Kalk et al (1975) described how tolbutamide injection elevated the plasma pancreatic glucagon level in patients with chronic pancreatitis. Samols et al (1969) reported a suppressive response of plasma IRG to tolbutamide in a case with glucagonoma.…”
Section: Immunochemical Analysis Of the Tissuesmentioning
confidence: 99%
“…In patients with chronic pancreatitis, elevated levels of pancreatic (or true) glucagon-like immunoreactivity (GLI) have been reported both in the fasting state (Kalk, Vinik, Bank, Buchanan, Keller andJackson 1974, Kalk, Vinik, Paul, Keller andJackson 1975) and in response to various stimuli (Kalk et al 1974(Kalk et al , 1975, Other workers have reported the presence of pancreatic GLI in the circu1ation of depancreatized dogs (Vranic, Pek and Kawamori 1974, Matsuyama and Foa 1974, Mashiter, Harding, Chou, Mashiter, Stout, DilJmond and Field 1975 and pancreatectomized humans (Muller, Brennan, Tan and Aoki 1974) using a pancreatic glucagon 'specific' antiserum. This pancreatic GLI may arise from a nonpancreatic source and is released in response to arginine stimulation in dogs (Mashiter et al 1975), but not in man (Muller et al 1974).…”
Section: Introductionmentioning
confidence: 99%